Pengaruh Kualitas Pelayanan Cabang Terhadap Nilai BSQ (Branch Service Quality) Di BCA KCP Malang - AGUS WIASTONO,; Dita Rachmawati, (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2022)
This study aims to know and analyze the Banking Quality Service (BSQ) to customer satisfaction and loyalty BCA KCP Malang. The population of this study as many as 126,356 customers in 2019. While the sample research of 401 people using the technique of Accidental sampling. Hypothesis testing was performed using partial least square data analysis (PLS) processed using Smart PLS 2.0. Dependent variable, namely banking service quality (BSQ) with effectiveness and assurance indicators, access, price embodiment, service portfolio, and reliability. While the independent variable consists of customer satisfaction (with indicator of form, reliability, responsiveness, assurance, empathy) and customer loyalty (with indicators of transaction habits, repeat transactions, recommendations, commitments).The results of the analysis of the banking service quality, satisfaction, and loyalty of customers obtained the findings empirically that satisfaction can mediate the influence of banking service quality on customer loyalty in a negative and significant. Where better banking service quality BCA KCP Malang will increase customer satisfaction so that it can also decrease loyalty.